(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
Globalization processes have a negative impact on the consciousness of young people, there is a disorientation of moral values. In modern society, spiritual poverty and immorality, ignorance is increasing, society is degrading, threatening our national identity and spiritual values.